First ladies - Truman, Margaret 1924-2008 (Random House, 1995)
This well-informed, intimate look at 29 women whose lives were intertwined with those who lead and have led this country presents forthright interviews with Lady Bird Johnson, Hillary Clinton, Nancy Reagan, and others, while warmly recalling Pat Nixon and Jacqueline Kennedy Onassis. Ms. Truman's legendary frankness is present but so, too, is a generosity of spirit. Photos throughout.--Publisher description.